Peran Dan Strategi Kepala Cabang Di Pegadaian Syariah Mandailing Natal - Mubarok, Hadi; Sitorus, Friska Olavia; Khairiyah, Imamah (LPPM Universitas Labuhanbatu, 2023)
Islam is a whole and integrated system and way of life, Islam provides dynamic guidance to all aspects of life including the business sector and financial transactions. This is seen by using the principles of Sharia, because it is expected that using the principles of Islamic Sharia can provide mashlahat for mankind and one of the advantages of Islamic financial institutions is not allowed to ask for excess of the loan principal, because such things include usury. As we know that riba in Islam is very forbidden. The development of Islamic financial institutions in Indonesia can be categorized as fast and one of the factors is the belief in the muslim community that conventional banking contains elements of usury which is prohibited by Islam.